#TITLE_ALTERNATIVE# - ANINDITA (NIM 10103013), PRADNYA
US Dollar to Rupiah currency rate is hard to predict and affected by many factors. One of the factor which affects currency rate fluctuation is Interest Rate Parity (IRP). IRP states that an appreciation or depreciation of one currency against another currency might be neutralized by a change in the interest rate differential. This final project builds an input-output system based on main principal of IRP, interest rate difference in US Dollar and Rupiah. The interest rate difference in US Dollar and Rupiah is set to be the input and exchange rate chose as output. As a seasonal modeling illustration, the system was built based on US Dollar and Rupiah interest rate and currency rate data from January 2006 to January 2007.